Evaluation of Microhardness in Conservative Root Dentin Treatment Techniques After Irrigation with Iron Oxide Nanoparticles Delivered with an External Magnetic Field - Ehsaan S. Al-Mustwfi; Hussain F. Al-Huwaizi (Applied Sciences)
Chemical endodontic irritants can lead to the demineralization of the inorganic tooth structure, its loss of integrity, microhardness changes, erosion, and an increased risk of fractures. We investigated the action of iron oxide nanomagnet particles (IONPs) as an irrigant solution for improving hardness and identifying the concentration of element ions in the root canal. There were six groups in total: a control group (no treatment) and experimental groups (UN: ultrasound agitation normal saline, UI: ultrasound agitation IONPs, MSI: magnetic field and endodontic needle with syringe agitation IONPs, MUI: magnetic field and ultrasound agitation IONPs, and EDTA: ethylenediaminetetraacetic acid). We hypothesized that IONPs with magnetic agitation would preserve microhardness better than EDTA. Vickers hardness testing was used to evaluate microhardness, which was then analyzed using energy-dispersive X-ray spectroscopy (EDS) to investigate the calcium/phosphorus ratio and the presence of iron. The IONP groups exhibit a higher VHN value than the EDTA group (p < 0.05). These results support our hypothesis, indicating that utilizing an IONP irrigant solution with an external magnetic field does not change microhardness but enhances it compared to the EDTA group, suggesting that employing an external magnetic field to deliver nanoparticles to the root canal wall does not affect the properties of the tooth structure compared to conventional instrumentation techniques, which lead to unnecessary loss of root structure.